Analysis of triage and care for women victims of road accidents - Fernanda Penido Matozinhos; Ingrid Raiana Silverio; Juliana Guilherme Boaventura; Thaís Moreira Oliveira; Thales Philipe Rodrigues da Silva; Allana dos Reis Corrêa
ABSTRACT Objective: to analyze the care flow for women victims of Road Traffic Accidents (RTA). Method: a descriptive study with 782 women victims of RAT, classified by the Manchester Triage System (MTS) between 2015 and 2016. The sociodemographic profile and the time between the stages of care were analyzed, as well as care place and outcomes. Results: of the women in the study, 65.47% were young adults, 80.44% lived without a partner and 62.28% lived in the city of Belo Horizonte. Regarding the time between recording and risk classification, the mean was 7.7 minutes (SD: 9.9). The prevalent flowchart was "Great Trauma" (62.92%). 53.07% had "Red/Orange" priority level and the most prevalent outcome was "Discharge after consultation/medication". Conclusion: the study shows that the hospital partially fulfills the times recommended by the MTS. Analyzing the flow of women victims of RAT contributed to optimize the quality and efficiency of care.